Endoscopic Treatment of Post-Cholecystectomy Biliary Leaks - Rio-Tinto,Ricardo (2021)
Abstract: Postcholecystectomy leaks may occur in 0.3-2.7% of patients. Bile leaks associated with laparoscopy are often more complex and difficult to treat than those occurring after open cholecystectomy. Furthermore, their incidence has remained unchanged despite improvements in laparoscopic training and technological developments. The management of biliary leaks has evolved from surgery into a minimally invasive endoscopic procedural approach, namely, endoscopic retrograde cholangiopancreatography (ERCP), which decreases or eliminates the pressure gradient between the bile duct and the duodenum, thus creating a preferential transpapillary bile flow and allowing the leak to seal. For simple leaks, the success rate of endotherapy is remarkably high. However, there are more severe and complex leaks that require multiple endoscopic interventions, and clear strategies for endoscopic treatment have not emerged. Therefore, there is still some debate regarding the optimal time point at which to intervene, which technique to use (sphincterotomy alone or in association with the placement of stents, whether metallic or plastic stents should be used, and, if plastic stents are used, whether they should be single or multiple), how long the stents should remain in place, and when to consider treatment failure. Here, we review the types and classification of postoperative biliary injuries, particularly leaks, as well as the evidence for endoscopic treatment of the latter.